Endothelial Cells: New Players in Obesity and Related Metabolic Disorders. (November 2018) - Graupera, Mariona; Claret, Marc
Abstract : Metabolic disorders such as obesity are accompanied by endothelial cell (EC) dysfunction and decreased vascular density. The current paradigm posits that metabolic alterations associated with obesity secondarily lead to EC dysfunction. However, in view of recent evidence reporting that EC dysfunction per se is able to cause metabolic dysregulation, this paradigm should be revisited and further elaborated. In this article we summarize current views and discuss evidence in favor of a causal role for ECs in systemic metabolic dysregulation. We also integrate and contextualize current research in a pathophysiological framework and discuss potential therapeutic strategies targeting angiogenesis to help to counteract obesity. Highlights: ECs are the metabolic gatekeeper of the organism. EC dysfunction is an early event in the pathogenesis of obesity. Modulation of vessel function is sufficient to regulate systemic energy balance. Thus, blood vessels have become a promising target for overcoming metabolic perturbations associated with obesity. In rodent models, inhibition of angiogenesis is a good therapeutic strategy in pre-existing obesity. Conversely, enhanced vessel growth protects against early exposure to a high-fat diet and in already obese mice.